2022
DOI: 10.3390/jof8050511
|View full text |Cite
|
Sign up to set email alerts
|

Production of Purpureocillium lilacinum and Pochonia chlamydosporia by Submerged Liquid Fermentation and Bioactivity against Tetranychus urticae and Heterodera glycines through Seed Inoculation

Abstract: Pochoniachlamydosporia and Purpureocilliumlilacinum are fungal bioagents used for the sustainable management of plant parasitic nematodes. However, their production through submerged liquid fermentation and their use in seed treatment have been underexplored. Therefore, our goal was to assess the effect of different liquid media on the growth of 40 isolates of P. lilacinum and two of P. chlamydosporia. The most promising isolates tested were assessed for plant growth promotion and the control of the two-spotte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…In the present study, we found that four pure VOCs induced both direct toxicity and adverse chemotaxis responses to M. incognita J2s, while these effects were compound and dose dependent. That VOCs can induce chemotaxis or repulsive effects in nematodes has been tested in a variety of systems 50–52 . Thus, as we showed that RKNs, such as M. incognita , suffered fitness consequences when in contact with these pure compounds, RKNs might try to avoid EPF via the observed repulsive behavior.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…In the present study, we found that four pure VOCs induced both direct toxicity and adverse chemotaxis responses to M. incognita J2s, while these effects were compound and dose dependent. That VOCs can induce chemotaxis or repulsive effects in nematodes has been tested in a variety of systems 50–52 . Thus, as we showed that RKNs, such as M. incognita , suffered fitness consequences when in contact with these pure compounds, RKNs might try to avoid EPF via the observed repulsive behavior.…”
Section: Discussionmentioning
confidence: 79%
“…That VOCs can induce chemotaxis or repulsive effects in nematodes has been tested in a variety of systems. [50][51][52] Thus, as we showed that RKNs, such as M. incognita, suffered fitness consequences when in contact with these pure compounds, RKNs might try to avoid EPF via the observed repulsive behavior. Interestingly, we also found that direct contact with pure VOCs inhibited egg hatching of RKNs, although only at high concentrations (100 mg/L).…”
Section: Nematicidal Activity Of Vocsmentioning
confidence: 80%
See 1 more Smart Citation
“…In general, drying blastospores is still a challenge [13], especially for large-scale processes and thus for commercially suitable products. In some studies, blastospores were dried in solid materials such as diatomaceous earth [45,46]. The viability of B. bassiana blastospores after air-drying and spray-drying was greater than 80% [45].…”
Section: Discussionmentioning
confidence: 99%
“…Purpureocillium lilacinum (syn. Paecilomyces lilacinus ) is a promising nematophagous fungus which remarkably suppresses various plant nematodes by parasitizing eggs and females, producing cell wall degrading enzymes and nematicidal metabolites [ 18 22 ]. However, in seriously infested soil, application of the biocontrol agents sometimes was unsuccessful [ 23 25 ].…”
Section: Introductionmentioning
confidence: 99%